A cross-layer cognitive radio-based framework and CAC scheme in WiMAX networks - Lu, Jinchang (2013)
Quality of service (QoS) provisioning is an important issue in the deployment of broadband wireless access networks with real-time and non-real-time traffic integration. The Connection Admission Control (CAC) operation is essential to guarantee the QoS requirements of connections while achieving system efficiency. Cognitive Radio is seen as a solution to the current low usage of the radio spectrum and the problem of the fixed spectrum allocation. In this paper, we propose a novel cross-layer Cognitive Radio-based QoS support framework and Cognitive Radio-based CAC scheme in WiMAX point-to-multipoint systems. By using a cross-layer approach, the proposed solution can intelligently explore unused spectrums and spread to non-active spectrums to improve the capacity of the system significantly and provide QoS guaranteed service to real-time traffic. A queueing analytical modeling for the WiAMX system has been carried out. The key system performance parameters are obtained based on the queueing analytical model theoretically. Extensive simulation experiments have been carried out to evaluate the performance of our proposal. The simulation results show that our proposed solution can expand the capacity of WiMAX systems up to two times while providing QoS guaranteed service to real-time and non-real-time traffics.